2019
DOI: 10.1002/cam4.2165
|View full text |Cite
|
Sign up to set email alerts
|

LncRNA‐LOC101928316 contributes to gastric cancer progression through regulating PI3K‐Akt‐mTOR signaling pathway

Abstract: Long noncoding RNA (lncRNA) has played the important function in regulation of various biological processes and in diagnostic value has been widely appreciated. In the present study, we have found that LOC101928316 was significantly downregulated in gastric cancer (GC) tissues specimen, GC cell lines, and associated with the GC patients tumor, node, and metastasis (TNM) stage and degree of differentiation ( P < 0.05). LOC101928316 overexpression can significantly inhibit SGC‐7901 cell mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
16
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 27 publications
1
16
0
Order By: Relevance
“…Recently, dysregulated lncRNAs have been presented to be implicated in the malignant progression of GC via affecting the PI3K/AKT/mTOR signaling pathway [ 39 ]. For example, lncRNA LOC101928316 facilitated the development of GC by modulating the PI3K/AKT/mTOR signaling pathway [ 12 ]; MALAT1/miR-183/SIRT1 axis contributed to the regulation of GC via PI3K/AKT/mTOR pathway [ 13 ] and lncRNA XLOC_006753 could induce cell proliferation, cell cycle, and metastasis but inhibit apoptosis in multidrug-resistant GC cells through promoting the PI3K/AKT/mTOR pathway [ 33 ]. NEAT1 has reported to activate the PI3K/AKT pathway to facilitate GC cell viability and migration [ 27 ].…”
Section: Discussionmentioning
confidence: 99%
“…Recently, dysregulated lncRNAs have been presented to be implicated in the malignant progression of GC via affecting the PI3K/AKT/mTOR signaling pathway [ 39 ]. For example, lncRNA LOC101928316 facilitated the development of GC by modulating the PI3K/AKT/mTOR signaling pathway [ 12 ]; MALAT1/miR-183/SIRT1 axis contributed to the regulation of GC via PI3K/AKT/mTOR pathway [ 13 ] and lncRNA XLOC_006753 could induce cell proliferation, cell cycle, and metastasis but inhibit apoptosis in multidrug-resistant GC cells through promoting the PI3K/AKT/mTOR pathway [ 33 ]. NEAT1 has reported to activate the PI3K/AKT pathway to facilitate GC cell viability and migration [ 27 ].…”
Section: Discussionmentioning
confidence: 99%
“…Gastric cancer (GC) is a prevalent malignancy and also one of the leading causes of cancer-generated death all around the world [1][2][3]. Like other carcinomas, GC is featured by infinite cell proliferation and tumor growth, which is attributed to the promotive influences of oncogenic regulators and the inhibitory influences of tumor-suppressive regulators [4][5][6]. In the current time, the main treatment methods for GC patients are surgical operation, chemotherapy and radiotherapy [7,8].…”
Section: Introductionmentioning
confidence: 99%
“…For example, a study showed that LOC101928316 regulates the progression of GC via modulating PI3K-Akt-mTOR signaling pathway. 34 A novel lncRNA TUBA4B can inhibit GC growth through regulating miR-214/miR-216a/b-PTEN axis. 35 Research also reported that lncRNA SEMA3B-AS1 regulates the proliferation of hepatocellular carcinoma cells by regulating miR-718/PETN axis.…”
Section: Discussionmentioning
confidence: 99%